Chronology and documentary handbook of the State of Georgia. - Frech, Mary L. (Chronologies and documentary handbooks of the States ;, 1973)
Contains a chronology of historical events from 1540 to 1970, a directory of prominent citizens, an outline of the state constitution, and copies of three historical documents.